Formação aeronáutica no Brasil: a segurança como princípio - Bertulucci, José Alberto Cesar (2024)
This research aims to investigate the main characteristics of aeronautical training and its relevance in relation to flight safety to the detriment of its proximity or distance from social and economic aspects. Within this broader context, we sought to analyze, in a more specific way, the curriculum and programmatic contents presented in the formulations of aeronautical courses relating to the different functions that may be developed and necessary for flight operations, evaluating technical skills , theoretical and practical, acquired by participants throughout the training course, both in flight and on the ground and in various other situations, covering the challenges and obstacles that may be faced in practice. We seek to focus on commercial air transport operations due to the fact that the most important onboard technologies and requirements regarding flight safety aspects are concentrated in this segment, providing aircraft with greater operating conditions, within automation, in the search for replacing actions human actions by operating systems driven by artificial intelligence, sensors and digital commands